Global Trends in the Development of Islamic Financial Institutions: Opportunities and Challenges in the Era of Globalization - Putra, Trisno Wardy; Majid, Jamaluddin; Kadir, Amiruddin (IAIN Kendari, 2025)
This study discusses the development of Islamic financial institutions in the era of globalization, including the opportunities and challenges they face. This study uses a descriptive approach with qualitative methods, which focuses on the analysis of secondary data from relevant literature. The results of the study indicate that Islamic financial institutions have great potential to continue to develop and make more significant contributions to society by understanding the dynamics of globalization and implementing appropriate strategies in optimizing their role in an inclusive and sustainable global financial system.